2017
DOI: 10.1016/j.jcrimjus.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The developmental and criminal histories of subgroups of sexual murderers engaging, or not engaging, in post mortem sexual interference, compared to rapists

Abstract: Identifying factors that may predict sexual aggression in the context of directly sexual murder, indirectly sexual murder, and non-fatal outcomes is necessary for advancing a field lacking a substantiated multifactorial theoretical model. Methods. Eighty-nine sexual murderers engaging in post mortem sexual interference were compared to 92 non-post mortem sexual interference sexual murderers and 72 rapists on developmental factors, adult lifestyle, and criminal history. An overall model was built using a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Meanwhile, the U.K. researchers constructed a database of 350 sexual murderers applying stringent inclusion criteria, focusing exclusively on adult-male, nonserial sexual murderers with female victims aged 14 and above. The data support the presence of differing pathways to sexual homicide (Stefanska, Carter, Higgs, Bishopp, & Beech, 2015) and differing psychosocial characteristics in subtypes of sexual murderers (Higgs, Stefanska, Carter, & Browne, 2017).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Meanwhile, the U.K. researchers constructed a database of 350 sexual murderers applying stringent inclusion criteria, focusing exclusively on adult-male, nonserial sexual murderers with female victims aged 14 and above. The data support the presence of differing pathways to sexual homicide (Stefanska, Carter, Higgs, Bishopp, & Beech, 2015) and differing psychosocial characteristics in subtypes of sexual murderers (Higgs, Stefanska, Carter, & Browne, 2017).…”
Section: Introductionsupporting
confidence: 54%
“…One study differentiating between subtypes of sexual murderers in comparison with non-homicide sexual aggressors found that while childhood adversity is common across the different groups, their psychosocial and criminal trajectories differ (Higgs, Stefanska, et al, 2017). Higgs and Stefanska (2018) present a multi-trajectory model of sexual aggression, suggesting that sexual murderers who most likely correspond to the sexualized killing subtype respond to early adversity by internalizing difficulties and becoming increasingly socially disconnected, experiencing difficulties in adulthood such as a lack of intimate relationships, eventually acting upon deviant, often sadistic, sexual drives.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are also very much motivated by ritualistic sexual fantasies where the degradation, humiliation, and suffering of their victims is sexually arousing. There has been empirical and theoretical exploration of the developmental antecedents of sexually sadistic behaviors, which indicate that many sexually sadistic offenders have unstable experiences in childhood and adolescence, they are socially isolated and adopt maladaptive coping behaviors and remain socially disconnected in adulthood both in terms of peer and intimate relationships (Higgs et al, 2015(Higgs et al, , 2017bLongpré et al, 2018). This provides evidence for the proposition that some sexually sadistic offenders may harbor considerable grievance toward the world or females in particular.…”
Section: Sexual Sadism Other Paraphilic Disorders and Grievance Fuele...mentioning
confidence: 99%
“…The termed ‘sexualised murder’ refers to crimes in which killings are inherently connected to sexual components (forced sexual acts accompanied by deviant sexual fantasy and violence) of the transgression (Higgs et al, 2017a: 1). Sexual murderers are mostly characterised by a lack of intimacy, sadistic and brutal acts, social isolation, sadistic fantasies, compulsive masturbation (hyper-sexuality) and personality disorders (an anxious personality profile of being avoidant, dependent and schizoid [emotional aloofness]) (Higgs et al, 2017b: 98). In the hours prior to the execution of the participant’s sexual crimes and murder, he articulated as experiencing a low sense of physical intimacy (i.e.…”
Section: Crimes and Criminal Recordmentioning
confidence: 99%